The prevalence of clinical signs of ankle instability in previously injured and uninjured ankles of club rugby players in South Gauteng - Mellet, Eloize (My University, 2010)
INTRODUCTION Rugby is a high impact sport with many injuries reported in the literature. A high rate of ankle injury is reported with resultant recurrence of these injuries. There is however only scarce epidemiological data with minimal detail to highlight clinical findings and prevalence of ankle injuries especially in the club rugby fraternity. AIMS This study investigated the prevalence of clinical signs of ankle injuries in rugby players at club rugby level in the South Gauteng region. The data collected was used to identify the clinical signs related to ankle instability for perceived, mechanical and functional parameters and was applied to determine the difference between players with and those without previous injury. METHODOLOGY The researcher obtained ethical clearance to do the study from the Human Research Ethics Committee of the University of the Witwatersrand. Permission was obtained from the Golden Lions Gauteng Rugby Union to use players in the South Gauteng region. One hundred and eighty players from nine clubs in the region participated in the study. Informed consent was obtained from all parties concerned and players were asked to complete a battery of tests. To determine the prevalence of clinical signs of perceived instability each player was asked to complete a data questionnaire and the Olerud and Molander questionnaire. The data questionnaire also included questions pertaining to the exclusion criteria. iii Objective testing was done to determine the clinical signs of mechanical instability of both ankles of each player through mechanical tests; the talar tilt and anterior drawer tests. Balance and proprioception were assessed through the Star Excursion Balance Test (SEBT) and Balance Error Scoring System (BESS) which is used to indicate clinical signs of functional instability and these tests were used to determine the prevalence of clinical signs of functional instability and to relate the clinical signs of functional instability to the other clinical findings. RESULTS The prevalence of ankle injuries at club rugby level is discussed for the different parameters of instability. The prevalence of clinical signs of perceived instability based on the Olerud and Molander questionnaire is 47%, as reported by the player and is further described in a sub-analysis of perceived problems. The prevalence of clinical signs of mechanical ankle instability, when laterality is ignored is 38.7%. The prevalence of clinical signs of functional ankle instability depends on the surface and the visual input and is greater as the challenge or protuberance increases in difficulty. The clinical signs of perceived, mechanical and functional ankle instability are further described and related to other clinical findings for two groups, namely those with and those without previous injury to the ankle and as expected clinically significant differences were noted with the players with previous injury recording a higher prevalence for perceived and mechanical parameters. The odds ratios for the presence of certain clinical signs revealed significant p-values for the presence of pain, stiffness and swelling and the need for supports e.g. bracing or taping and the affect on activities of daily living. DISCUSSION In this study there is a high prevalence of clinical signs of ankle instability in club rugby players for perceived, mechanical and functional parameters, compared to the prevalence reported in the literature. From the study the clinical findings associated with the presentation of ankle injuries in club rugby players have been established and related to the perceived, mechanical and functional signs of instability. Differentiation between players with reported ankle injury and those without were also done and significant differences were noted between the two groups for perceived and mechanical parameters but where the functional assessment was done it supported the fact that balance and proprioception tests included the whole kinetic chain and does not view the ankle in isolation. It was evident that previously injured players were more likely to sustain future injury to the ankle and odds-ratios to support this showed an increased risk of the presence of swelling, stiffness and pain for players with previous injury and the greater need for the use of supports and influence on activities of daily life. The information gathered can be used in the future to set up a management plan for pre-season screening, assessing and addressing individual predisposing biomechanical factors, managing acute injuries successfully and rehabilitation in the post-season phase.
MSc Physiotherapy, Faculty of Health Sciences, University of the Witwatersrand, 2009.
Keywords: functional instability; mechanical instability; ankles; rugby players